Utilisation of Analytic Hierarchy Process in Determining Natural Disaster Evacuation Points - Sandhy Fernandez; Muhamad Awiet Wiedanto Prasetyo; Argiyan Dwi Pritama (Universitas Negeri Semarang, 2024)
The positive impact of the dry season in Indonesia is that the tourism sector, which prefers to travel to beaches, islands and other tourist attractions, becomes busier and activities such as surfing and diving are usually better during the dry season. Another negative impact is the natural disaster of forest fires and dry peatlands which are highly flammable and cause damage to the natural environment, reduce air quality and threaten wildlife habitats. The most frequent natural disasters in Indonesia are floods, which have a significant impact on health problems because polluted flood water can cause water diseases such as diarrhea, skin infections and even threaten people's lives. Determining the best evacuation point in the context of disaster mitigation is a complex and critical decision. The Analytic Hierarchy Process (AHP) method is a decision analysis method that makes it possible to compare several different criteria that are relevant in decision making, very helpful for determining the most effective alternative. The existing calculation results are added from each existing sub-criteria, the Supermarket alternative result is 0.27, the Hill alternative result is 0.45, the Health Center alternative result is 0.03, the Place of Worship alternative result is 0.30, the Government Building alternative result is 0.28. If the largest value is ranked to the smallest value, Alternative Bukit is the best evacuation place in the event of a natural disaster.